2018
DOI: 10.1002/mnfr.201700771
|View full text |Cite
|
Sign up to set email alerts
|

Synergetic Effects of Prenatal and Postnatal High Sucrose Intake on Glucose Tolerance and Hepatic Insulin Resistance in Rat Offspring

Abstract: Both prenatal and prenatal-plus-postnatal high sucrose exposure substantially affect biological functions related to insulin homeostasis. IRS-1(S612) protein phosphorylation appears to be a part of the molecular mechanism underlying these effects. These results add to the understanding of how high sucrose intake contributes to insulin resistance and diabetes pathogenesis and how postnatal nutrition and lifestyle may mitigate detrimental prenatal exposures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 31 publications
0
19
0
Order By: Relevance
“…Although several terms for mice were included in the database search, only rat studies were identified. Eleven of the included papers used Sprague-Dawley rats, 31,[38][39][40][41][42][43][44][45][46][47] three used Wistar rats 30,48,49 and one did not report strain type. 29 Sucrose was administered at either 10% w/v [29][30][31]48,49 or 20% w/v 29,[38][39][40][41][42][43][44][45][46][47] and maternal exposure ranged from 16 to 126 days, including periods during pre-conception, gestation and lactation.…”
Section: Study Characteristics and Designmentioning
confidence: 99%
See 2 more Smart Citations
“…Although several terms for mice were included in the database search, only rat studies were identified. Eleven of the included papers used Sprague-Dawley rats, 31,[38][39][40][41][42][43][44][45][46][47] three used Wistar rats 30,48,49 and one did not report strain type. 29 Sucrose was administered at either 10% w/v [29][30][31]48,49 or 20% w/v 29,[38][39][40][41][42][43][44][45][46][47] and maternal exposure ranged from 16 to 126 days, including periods during pre-conception, gestation and lactation.…”
Section: Study Characteristics and Designmentioning
confidence: 99%
“…Eleven of the included papers used Sprague-Dawley rats, 31,[38][39][40][41][42][43][44][45][46][47] three used Wistar rats 30,48,49 and one did not report strain type. 29 Sucrose was administered at either 10% w/v [29][30][31]48,49 or 20% w/v 29,[38][39][40][41][42][43][44][45][46][47] and maternal exposure ranged from 16 to 126 days, including periods during pre-conception, gestation and lactation. The majority 29,30,[32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47] employed a compulsory drinking paradigm with sucrose solution being the only source of drinkin...…”
Section: Study Characteristics and Designmentioning
confidence: 99%
See 1 more Smart Citation
“…When the pregnant dam consumes a larger quantity of sugar during pregnancy, metabolic changes in the pups may persist during post-natal life. This affects pancreas development and glucose tolerance in male offspring [38]. In addition, when offspring have been exposed to high sucrose during gestation, exposure to high sucrose later in adulthood worsens glucose tolerance.…”
Section: Influence Of Dietary Intakes During Gestation and Or Lactmentioning
confidence: 99%
“…In addition, when offspring have been exposed to high sucrose during gestation, exposure to high sucrose later in adulthood worsens glucose tolerance. This could be explained by a default of hepatic insulin signaling [38]. Sugar consumption by rat dams during gestation and lactation induces an increase in body weight, blood glucose and plasma insulin levels in mothers and pups in a dose-dependent manner [39].…”
Section: Influence Of Dietary Intakes During Gestation and Or Lactmentioning
confidence: 99%